2014
DOI: 10.1161/strokeaha.113.003826
|View full text |Cite
|
Sign up to set email alerts
|

Thrombelastography Detects Possible Coagulation Disturbance in Patients With Intracerebral Hemorrhage With Hematoma Enlargement

Abstract: Background and Purpose Intracerebral hemorrhage (ICH) has high morbidity and hematoma enlargement (HE) causes worse outcome. Thrombelastography (TEG™) measures the dynamics of clot formation and dissolution, and might be useful for assessing bleeding risk. We used TEG™ to detect changes in clotting in patients with and without HE after ICH. Methods This prospective study included 64 patients with spontaneous ICH admitted from 2009 to 2013. TEG™ was performed within 6 hours of symptom onset and after 36 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 25 publications
3
36
2
Order By: Relevance
“…We screened 4191 studies identified by our searches, assessed 167 for eligibility, invited 77 eligible cohorts to share data, and obtained patient-level data from 36 (47%) cohorts18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51 involving 6428 patients with repeat brain imaging after intracerebral haemorrhage between 1985 and 2015 (no data up to 1984 were obtained; figure 1; appendix). 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55 Countries classified as high income by the World Bank contributed to 26 (72%) of 36 collaborating cohorts versus 30 (73%) of 41 eligible cohorts that did not collaborate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We screened 4191 studies identified by our searches, assessed 167 for eligibility, invited 77 eligible cohorts to share data, and obtained patient-level data from 36 (47%) cohorts18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51 involving 6428 patients with repeat brain imaging after intracerebral haemorrhage between 1985 and 2015 (no data up to 1984 were obtained; figure 1; appendix). 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55 Countries classified as high income by the World Bank contributed to 26 (72%) of 36 collaborating cohorts versus 30 (73%) of 41 eligible cohorts that did not collaborate.…”
Section: Resultsmentioning
confidence: 99%
“…20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55 Countries classified as high income by the World Bank contributed to 26 (72%) of 36 collaborating cohorts versus 30 (73%) of 41 eligible cohorts that did not collaborate. Planimetric methods of measuring intracerebral haemorrhage volume were used by 19 (53%) of 36 collaborating cohorts versus six (15%) of 41 eligible cohorts that did not collaborate.
Figure 1Study selection*Excluded studies and cohorts are listed in the appendix.
…”
Section: Resultsmentioning
confidence: 99%
“…Patients with HE had a baseline K and delta that were longer compared to the HE negative patients. At 36 h, TEG was not different between the two groups (as it was at 6 h) [19]. At the present time we know of no studies that utilize TEG to describe fibrinolysis in ICH.…”
Section: Intracerebral Hemorrhage (Ich)mentioning
confidence: 62%
“…The myriad disorders, which may affect the coagulation cascade, have led to the development of more refined laboratory testing methods to detect and track its function. One of the most widely adopted of these is thromboelastography (49), a modality that detects variables such as the rate of fibrin formation, the thrombin burst, and the firmness of the resultant clot (50). Such tests may allow for the stratification of patients at risk of hematoma enlargement and represents an area for future study (50).…”
Section: Pathophysiology Of Hematoma Expansionmentioning
confidence: 99%